Clockwork : or all wound up - Pullman, Philip, 1946- (Arthur A. Levine Books, 1998)
Long ago in Germany, a storyteller's story and an apprentice clockwork-maker's nightmare meet in a menacing, lifelike figure created by the strange Dr. Kalmenius.